2020
DOI: 10.1111/ffe.13230
|View full text |Cite
|
Sign up to set email alerts
|

An efficient fatigue and creep‐fatigue life prediction method by using the hysteresis energy density rate concept

Abstract: Fatigue damage, time-dependent creep damage and their interaction are considered as the main failure mechanisms for many high temperature structural components. A generalized methodology for predicting both the high temperature low cycle fatigue (HTLCF) and creep-fatigue lives by using the hysteresis energy density rate (HEDR) and fatigue damage stress concepts was proposed.Experimental data for HTLCF and creep-fatigue in Alloy 617, Haynes 230 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…More reliable estimation performance could be further achieved by combining the proposed model with some probabilistic approaches. Considering the diversities in material characteristics and loading conditions, more investigations are necessary in the future to evaluate the universality of the proposed model for different application scenarios, particularly for high-temperature fatigue issues in which the strain or energy rate plays an important role (Wang et al., 2020b).…”
Section: Model Evaluations and Comparisonsmentioning
confidence: 99%
“…More reliable estimation performance could be further achieved by combining the proposed model with some probabilistic approaches. Considering the diversities in material characteristics and loading conditions, more investigations are necessary in the future to evaluate the universality of the proposed model for different application scenarios, particularly for high-temperature fatigue issues in which the strain or energy rate plays an important role (Wang et al., 2020b).…”
Section: Model Evaluations and Comparisonsmentioning
confidence: 99%
“…Fatigue-creep interaction is a key factor for the failure of many engineering components and structures under high temperature and cyclic loading. 34,35 In this study, highfrequency induction heating was used to model the thermal shock process of the piston. The temperature changed so quickly that it was difficult to maintain 350 C for 1-3 min.…”
Section: Limitations and Potential Improvementsmentioning
confidence: 99%
“…[5][6][7][8] Creep-fatigue interaction is a typical damage mode of turbine components, and attracts numerous attentions. [17][18][19][20] Wang et al 17 proposed a creep-fatigue life estimation model using the concept of the hysteresis energy density rate. Rai et al 18 experimentally investigated the creep-fatigue deformation micromechanisms of CM 247 DS LC alloy and suggested that the generation of dislocation substructures changed with the dwell times.…”
Section: Introductionmentioning
confidence: 99%
“…Creep‐fatigue interaction is a typical damage mode of turbine components, and attracts numerous attentions 17–20 . Wang et al 17 proposed a creep‐fatigue life estimation model using the concept of the hysteresis energy density rate.…”
Section: Introductionmentioning
confidence: 99%